2002
DOI: 10.1080/08910600260081720
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Controlled Trial of a Probiotic Lactobacillus Strain in Healthy Adults: Assessment of its Delivery, Transit and Influence on Microbial Flora and Enteric Immunity

Abstract: In severa l intestinal disease states, altered micro ora, impaired gut barrier and:or intestinal in ammation offer a rationale for the effective therapeut ic use of probiotic microorganisms. However , for most candidat e probiotic organisms there is a lack of evidence detailing their characterisation and effects on host ora and immunity. We have previously reported the isolation and characterisation, from surgically resected segment s of the huma n gastrointestinal tract (GIT), of potential probiotic lactic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 36 publications
(37 reference statements)
4
29
0
1
Order By: Relevance
“…There has been unresolved speculation as to whether the health benefits associated with probiotic consumption are dependent on the microorganisms becoming long-term residents in the gut. However, in this study the introduced lactobacilli were detected at levels comparable to those observed in the previously reported studies (24,36), and they remained recoverable, at least at low levels, for a period of 7 days after cessation of consumption. This suggests that continual ingestion of beneficial microbes will probably be required for most individuals if probiotics in their current form are to be exploited for enhancement of health.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There has been unresolved speculation as to whether the health benefits associated with probiotic consumption are dependent on the microorganisms becoming long-term residents in the gut. However, in this study the introduced lactobacilli were detected at levels comparable to those observed in the previously reported studies (24,36), and they remained recoverable, at least at low levels, for a period of 7 days after cessation of consumption. This suggests that continual ingestion of beneficial microbes will probably be required for most individuals if probiotics in their current form are to be exploited for enhancement of health.…”
Section: Discussionsupporting
confidence: 90%
“…As in previous studies completed in healthy volunteers (36) and mild-moderately active Crohn's disease patients (24), the probiotic bacteria were administered to the ulcerative colitis patients as components of a fermented milk product. There has been unresolved speculation as to whether the health benefits associated with probiotic consumption are dependent on the microorganisms becoming long-term residents in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent survival of L. casei DN-114 001 Rif was greater during the first 2 h of collection (51.2% to 10.0%) than what had been previously reported for other lactobacilli in the ileum (e.g., 0.5% for Lactobacillus fermentum KLD [24]; 1.5% for a commercial strain of Lactobacillus acidophilus [16]) or in the small intestine (e.g., 7% and 11.8% for Lactobacillus plantarum NCIMB 8826 [24] and for Lactobacillus salivarius UCC118 [5], respectively).…”
mentioning
confidence: 66%
“…This has been demonstrated for a number of bacteria, including Escherichia coli, where colicin producers were more persistent than nonproducers (16), and Streptococcus mutans, where a mutant with enhanced mutacin production was more successful at colonizing the oral tract than the wild-type strain (18). UCC118 is strongly adherent to epithelial cells (47) and is known to be able to persist in the gut for a substantial length of time after ingestion (8). The induction of bacteriocin gene expression reported here is likely to enhance the colonization potential of L. salivarius through inhibition of competing organisms and may well be a factor in the persistence of UCC118 in the gastrointestinal tract (GIT).…”
Section: Resultsmentioning
confidence: 97%